A family empowerment in increasing pregnant women's interest in carrying out anc in South Nias district - Yarniwati Hondro; Tan Suyono; Mangatas Silaen (Jurnal Scientia, 2024)
In a preliminary study at 6 Community Health Centers, 30 pregnant women experienced anemia caused by mothers rarely going to check their pregnancy at a Public health center. This research aims to design a family empowerment strategy to increase pregnant women's interest in carrying out ANC in South Nias Regency. There were 10 research participants. Data were analyzed univariately, bivariately, and multivariately as well as by theme analysis. The results of the research show that the implementation of ANC is not by the schedule determined by doctors and health workers, this can be seen in the informants' statements, The family accompanies pregnant women to do ANC, Transportation is an obstacle in doing ANC, When doing ANC, time is one of the factors inhibitor. This research concludes that the right strategy is to increase family empowerment, such as providing continuous health education to empowered families. Suggestion-namely for health workers routinely provide health education to families with pregnant women. Dna continues to evaluate the implementation of ANC according to the 10 indicators in the KIA book and provides training to health workers on good and correct services.